What Do Elementary Teachers Think about Teacher Reflection? - Droguett Araya, Valentina (2023)
This qualitative research aims to analyze the perceptions of elementary teachers regarding the usefulness of teacher reflection. The authors collected the data through the application of semi-structured interviews with 18 teachers from different schools in Santiago, Chile. In addition, through thematic analysis, the researchers identified three main themes: obstacles, usefulness, and moments in which teachers reflect, composed of four and three codes, respectively. Time, space, affinity, and disposition were identified as obstacles. Innovation, improvements in student learning, and professional development were highlighted as useful outcomes of teacher reflection. Regarding moments, reflection in action, on action, and for action were emphasized. Based on the results, the authors concluded that the reflective process is essential in teaching, and the importance of strengthening a continuous reflective process by teachers is emphasized to promote optimal pedagogical practices.